RANCANG BANGUN SISTEM INFORMASI UKK MANDIRI SMK BERBASIS WEB DENGAN INTEGRASI ADDIE DAN SCRUM - Firdaus, Alamsyah; Muhammad, Taofik; Habibie, Alfadl; Amirulloh, Imam; Rusilpan, Ilpan (INTI Nusa Mandiri, 2026)
The digital transformation of vocational education necessitates competency-based assessment systems that are integrated, accountable, and data-driven. This study develops a web-based UKK Mandiri Information System through an integrative ADDIE–Scrum formulation that operationally maps the relationship between instructional design for competency assessment and iterative software engineering processes. A Research and Development (R&D) approach was employed, involving needs identification through interviews, observations, and document analysis within the implementation context of UKK Mandiri at SMK YPC Tasikmalaya. The system was developed using a three-tier architecture with role-based access control and an automated competency achievement validation mechanism. Testing results demonstrate functional conformance across all core modules, cross-browser compatibility, and baseline security validation. Expert evaluation yielded a mean score of 4.40 (SD = 0.72; α = 0.91; 95% CI [3.89–4.91]), categorized as “Highly Feasible.” The findings indicate improved administrative efficiency, consistency in score calculation, and enhanced traceability of competency assessments, while reinforcing the integration between instructional design and agile software development through a documented and replicable coordinative model